Voice and Identity: Authoring the Self through Language Exchange - Ahsani, Nizam; Budairi, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The proliferation of digital technology and the internet have afforded people from multiple spatial locations and cultural boundaries the opportunity to interact and share ideas, life stories and practices. This article reports on an online journey of a 19-yearl-old EFL university student, Nadia, who engaged in a community of practice of language learners mediated through an online platform called mylanguageexchange.com. The data were collected through a connective ethnography approach involving the use of WhatsApp chats, emails and unstructured informal interviews via mobile phone call. Drawing on Bakhtinian perspective of dialogism, the data analysis revealed the extent to which Nadia was able to (re) author her voices and enact identity L2 user through his participation in the community of practice. Nadia’s accounts also bear a palpable sense of internal struggle with a variety of competing discourses, rendering her utterances heteroglossic. In view of learning, the data analysis revealed the role of participation in a community of practice as a mediational tool to facilitate the transfer of linguistic knowledge and skills from the social plane to the individual through inter-mental and intra- mental process. The article concludes with recommendations to look at out of school literacy practice and digital space as a rich site for self-authoring and L2 identity formation and to adopt a third space pedagogy which disrupts the binary categorization of L2 user as ‘good’ vs ‘poor’ or ‘legitimate’ vs ‘illegitimate’.